2015
DOI: 10.15376/biores.10.2.2626-2641
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Hemicelluloses and Lignin from Rice Straw by Combining Autohydrolysis and Optimised Mild Organosolv Delignification

Abstract: An integrated strategy was followed to valorise rice straw, one of the most relevant biomass feedstocks available worldwide, to selectively recover solubilised hemicelluloses and lignin. The pathway encompassed the use of autohydrolysis to hydrolyse the hemicelluloses and an ethanol-based organosolv process to solubilise lignin. Several autohydrolysis conditions were assayed with the best results obtained at 210 ºC (log R0 4.15), which enabled high removal of hemicelluloses, yielding an oligosaccharide-rich hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 37 publications
3
23
0
1
Order By: Relevance
“…it is significantly higher than the glucose yieldreported for eucalyptus residues (54%), and close to 82% for olive tree pruning, and only slightly lower for straws (88, 90 and 91 %, respectively for rice, corn straw and wheat straw) [37][38][39], what may be explained by the higher lignin content of the cherimola seed cake as compared to straws.Although, it is reported that the highest glucose yield can only be achieved after the complete removal of hemicellulose, the lignin also plays a role on preventing cellulose hydrolysis that must not be neglected [22].…”
Section: Enzymatic Digestibility Of the Solid Residuesmentioning
confidence: 72%
“…it is significantly higher than the glucose yieldreported for eucalyptus residues (54%), and close to 82% for olive tree pruning, and only slightly lower for straws (88, 90 and 91 %, respectively for rice, corn straw and wheat straw) [37][38][39], what may be explained by the higher lignin content of the cherimola seed cake as compared to straws.Although, it is reported that the highest glucose yield can only be achieved after the complete removal of hemicellulose, the lignin also plays a role on preventing cellulose hydrolysis that must not be neglected [22].…”
Section: Enzymatic Digestibility Of the Solid Residuesmentioning
confidence: 72%
“…A hydrothermal treatment could be considered for removal of hemicelluloses and could give rise to oligosaccharides (Moniz et al 2013(Moniz et al , 2014. Delignification via solvolysis (Moniz et al 2015) would yield organosolv lignin in solution and a solid fraction of cellulose. A schematic potential valorization design is given in Figure 1 showing potential estimates of maximal yields for the different products.…”
Section: Bark Valorization Potentialmentioning
confidence: 99%
“…In the case of G. glabra bark, the high content of polar extractives motivates their removal and valorisation as a first step in the conversion process, while the high content of lignin could be of interest for, e.g., biofuel production, and the xylans can be a source of xylo-oligosaccharides and other sugars (Moniz et al 2013(Moniz et al , 2014(Moniz et al , 2015.…”
Section: Chemical Compositionmentioning
confidence: 99%